The Effect of Different doses of rElGH (rekombinat Ephinephelus lanceolatus Growth Hormone) on Growth and Survival of Pomfret fish in Recirculation Systems - Ebbin M. SIlalahi; Usman M. Tang; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The study wasconducted from 3stof May to 10th June 2017.The research to do cultivation technology faculty of fisheries and marine University of Riau.The research was conducted to determine the dose of recombinant growth hormone (rGH) of Ephinepelus lanceolatus supplemented in the commercial diet that generates the best performance on body weight, body length, specific growth rate, survival rate, feed efficiency, and feed convertion rate of river Bawal Air Tawar (Colossoma macroponum)in resirculation system.The dose of rElGH administrated was 1, 2, 3 and 4 mg/kg of commercial feed and no rGHsupplementation as control. Each treatment was design in triplicates. Pomfret fish at average 3-4 cm were reared in aaquarium in a density 10 fish/aquarium for 30 days. The fish were fed with the rElGH suplplemented diet once a three days at satiation. The results showed that growth body weight of 2 mg/kg feed was (8,25g), Specific growth rate 9,21 %, feed efficiency (107,7%), Feed convertion rate (0,96%),(P<0.05) than other treatment.Length of 2 mg/kg feed was 4,02 cm higher than other treatment, Survival rate of 3 mg/kg feed was 100 %.(P>0.05) than other treatment. Thus, supplementation rGH 2 mg/kg feed of Pomfret fish once in three days can be applied in enhance the growth Pomfret fish with a best performance of growth.Keyword: Pomfret fish, recombinant growth hormone, resirculation system